Dynamics, Implications and Management Strategies of Transport Constraints in Fako Division, South West Region-Cameroon - Tufoin Kilian Diang; Dr. Tosam Hycinth Ngong; Ngwa Patience Lum; Ajukebi Linda Ebob; Dr. Ndi Roland Akoh, (Indian Journal of Transport Engineering (IJTE), 2023)
Transport dynamics and management strategies of emerging constraints for efficiency and development is critical. When transport systems are poorly integrated with insufficient infrastructure, worst of all in the mist of insecurity, it hinders mobility, production and distributions making development to be stunted. It was against this premise that this study was designed to investigate the dynamics, implications and constraints confronting the transport sector in Cameroon and in Fako Division in particular. These are key issues that cannot be relegated to the footnotes and if actions are not taken development will be dared. Data for this study were sourced from secondary and primary sources. Secondary data were obtained from exploration of published and unpublished documents relevant to the study. Reports, journals, articles, decrees made up some of these documents. Primary data were sourced from field surveys where a convenient sampling technique was used to administer 313 copies of questionnaires to 10 sampled localities in Fako Division. Auxiliary primary data were gotten via interviews and observations in motor parks and ports and along the Fako coast. Results indicated that the transport sector in Fako Division is dynamic and have induce and plethora of related activities since it is derived demand. Response score revealed (52% and 41%) of high appreciation and appreciation respectively to the relevance of transport in trade and commerce. emerging constraints were noted to be; insecurity, depreciating infrastructure and loosely integrated systems of transport which is bogging down mobility, efficiency and effectiveness of the transport sector in the Division. Also, results noted that management strategies of the emerging challenges transcends to curbing insecurity, improving transport infrastructure to effectively integrating transport modes and systems. Furthermore, revamping the secondary ports (Tiko, Limbe and Idenau), construction and rehabilitation of road edges and vertices can improve the functional and transactional operations of the transport sector in Fako Division and in Cameroon in general. This study recommends an effective integration and improvement of transport infrastructure in Fako Division to boost the transport sector to be more dynamic and efficient to induce development.